2011
DOI: 10.1002/app.35010
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, structural, and optical properties of γ‐irradiated poly(vinyl alcohol)/poly(ethylene glycol) thin film

Abstract: Poly(vinyl alcohol)/poly(ethylene glycol) (PVA/PEG) copolymer was prepared using casting technique. The obtained PVA/PEG thin films have been irradiated with gamma rays with doses ranging from 1.5 to 20 Gy. The resultant effect of gamma irradiation on the thermal properties of PVA/PEG has been investigated using thermogravimetric analysis (TGA) and differential thermal analysis (DTA). The onset temperature of decomposition T o and activation energy of thermal decomposition E a were calculated, results indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…[12][13][14] In our previous work, we studied the thermal and structural properties of gamma-irradiated PVA/poly(ethylene glycol) thin film. 15 It is found that the stabilization of PVA using both different additives and irradiation is required. In the present paper, modifications in the structural and optical properties of PVA due to Cr 2 O 3 nanoparticles concentration and gamma irradiation have been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] In our previous work, we studied the thermal and structural properties of gamma-irradiated PVA/poly(ethylene glycol) thin film. 15 It is found that the stabilization of PVA using both different additives and irradiation is required. In the present paper, modifications in the structural and optical properties of PVA due to Cr 2 O 3 nanoparticles concentration and gamma irradiation have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Cr 2 O 3 nanoparticles have been prepared and characterized by several researchers . In our previous work, we studied the thermal and structural properties of gamma‐irradiated PVA/poly(ethylene glycol) thin film . It is found that the stabilization of PVA using both different additives and irradiation is required.…”
Section: Introductionmentioning
confidence: 99%
“…7 PANI has also remarakable values of dielectric and tensile strength as well as the good electrical and mechanical properties. [8][9][10] In order to create a nanocomposite polymer gel with strong ionic conductivity and good mechanical integrity, Patel et al examined the combined form of gel and composite polymer. 17 Shrivastava et al used UV-Vis absorption spectroscopy and spectroscopic ellipsometry measurements to report the optical properties of the polymer nanocomposites in thin film and powder form.…”
Section: Introductionmentioning
confidence: 99%
“…Also, PANI has a good filming ability when it is blended with other polymers 7 . PANI has also remarakable values of dielectric and tensile strength as well as the good electrical and mechanical properties 8–10 . In order to create a nanocomposite polymer gel with strong ionic conductivity and good mechanical integrity, Patel et al examined the combined form of gel and composite polymer 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies are reported by other investigators where the changes of various properties of SPTDs due to protons and electrons [16], gamma radiations [17,19,20], alpha particles [21] and heavy ions [22][23][24] are characterized. In case of low LET radiations such as electrons and gamma, the distribution of ionization products along the tracks is more uniform than in case of heavier charged particles [25].…”
Section: Introductionmentioning
confidence: 99%